APLIKASI JADWAL DAN PENILAIAN SKRIPSI UNIVERSITAS NURDIN HAMZAH: Web-Based Application, Thesis Scheduling, Thesis Assessment, Academic Information System, User Acceptance Test (UAT) - Sany, Ezrifal (LP2M Universitas Nurdin Hamzah, 2025)
This research aims to develop a web-based application to support the scheduling and assessment of thesis defenses at Universitas Nurdin Hamzah. The current scheduling process is conducted manually, often resulting in conflicts between supervisors, examiners, rooms, and students. In addition, thesis assessment is still carried out using printed forms, which are prone to recording errors and delays in result compilation. The developed application was designed to address these issues by providing two main modules, namely a thesis scheduling module and a thesis assessment module. The development methodology applied the System Development Life Cycle (SDLC) with a Waterfall approach, covering requirement analysis through system testing. The system was evaluated using black-box testing for functionality validation and a User Acceptance Test (UAT) involving 30 respondents, including lecturers, students, and academic staff. The results showed that 92% of the system’s functions performed as expected, while user satisfaction reached 90%. Furthermore, the application successfully accelerated the scheduling process by up to 60% compared to manual methods. Therefore, this application improves efficiency, accuracy, and transparency in managing thesis defenses.